Dinamika Kebahagiaan Siswa dalam Penjurusan di SMK - Yunika, Emalia; Sri Ernawati; Dhian Riskiana Putri (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This research was made with the aim of looking at the dynamics of happiness in school majors. The research method used is descriptive qualitative method by means of observation, interview and documentation. The research informants consisted of 6 informants (4 main informants, 2 supporting informants). The results of this study indicate that students at SMK AL-ISLAM Surakarta feel quite happy when they do study majors. Where in the aspect of positive social relations shows a high role, students can feel that they feel supported and accepted by their friends, teachers and family. The resilience aspect is the second aspect that has a high role in student happiness in their majors. Where students can adapt, and are able to rise when experiencing difficult experiences, especially in the learning process in their majors. Keywords: Happiness, Majoring, SMK, Students.